Improving Employee Performance Based on Delegative Leadership Style and Work Environment - Mujiono, Mujiono; Mustikasari, Sovita; Prahastyo, Puji; Prasetyo, Imam Dwi; Qomariah, Nurul (Budapest International Research and Critics University, 2024)
Employee performance is an important thing that needs to get attention from an organization in achieving the goals it wants to achieve. The design objective of this research is to determine the impact of delegative leadership and work environment on employee performance among sub-district employees in Jember Regency. The population of this research is all sub-district employees in Jember Regency. The data analysis design includes descriptive analysis, validity and reliability tests and hypothesis testing. This research produces research hypotheses, including the first hypothesis, namely that delegative leadership has a positive impact on employee performance. The second hypothesis states that the work environment has a positive impact on employee performance.